From Speech to Underwater Acoustics: A Transfer Learning Framework for Real-Time Passive Diver Detection Using Keyword Spotting Models - Deeb, Osama; Mahmoud, Saier; Saleh, Louay; Jafar, Assef; Al Dakkak, Oumayma; Chouaib, Ibrahim (Archives of Acoustics, 2026)
Passive acoustic detection of divers faces challenges such as low signal-to-noise ratios (SNRs), data scarcity, and latency in conventional methods. This paper proposes keyword spotting for diver detection (KWS-DD) – a transfer learning framework that repurposes speech-oriented KWS models for data-efficient diver detection. Diver inhalation signatures are treated as acoustic ‘keywords,’ enabling adaptation of the transformer-based HuBERT architecture (pre-trained on speech) to identify quasi-periodic respiratory events in underwater audio. The core innovation of this work lies in adapting the state-of-the-art speech model HuBERT for accurate diver detection via non-speech inhalation acoustics. This approach eliminates the need for accumulation during the respiratory cycle, enabling real-time detection using a minimal amount of domain-specific data (120 inhalation samples). The solution, deployed in diverse marine conditions, achieved 94.4 % accuracy and 94.6 % F1-score for inhalation sounds. This represents a more than 50 % range extension over conventional methods, which proved unreliable at distances greater than 10 meters in low-SNR environments. The framework reduces false alarms caused by boat noise and generalizes to external datasets, validating cross-domain transferability. This work bridges AI-based speech processing and passive sonar signal processing, offering a resource-efficient solution for real-time underwater surveillance.